Kinetic and economic analysis of reactive capture of dilute carbon dioxide with Grignard reagents - Dowson, G.R.M.; Dimitriou, Ioanna; Owen, R.E.; Reed, D.G.; Allen, Raymond W.K.; Styring, P. (Royal Society of Chemistry, 2015)
Carbon Dioxide Utilisation (CDU) processes face significant challenges, especially in the energetic cost of carbon capture from flue gas and the uphill energy gradient for CO2 reduction. Both of these stumbling blocks can be addressed by using alkaline earth metal compounds, such as Grignard reagents, as sacrificial capture agents. We have investigated the performance of these reagents in their ability to both capture and activate CO2 directly from dried flue gas (essentially avoiding the costly capture process entirely) at room temperature and ambient pressures with high yield and selectivity. Naturally, to make the process sustainable, these reagents must then be recycled and regenerated. This would potentially be carried out using existing industrial processes and renewable electricity. This offers the possibility of creating a closed loop system whereby alcohols and certain hydrocarbons may be carboxylated with CO2 and renewable electricity to create higher-value products containing captured carbon. A preliminary Techno-Economic Analysis (TEA) of an example looped process has been carried out to identify the electrical and raw material supply demands and hence determine production costs. These have compared broadly favourably with existing market values.